Experimental Verification Of Nickel-Metal Hydride Battery Parameters Estimation - Mohamad Basir, Muhammad Sufyan Safwan; Abdullah, Abdul Rahim; Ranom, Rahifa; Kasim, Rizanaliah; Selamat, Nur Asmiza; Shamsudin, Nur Hazahsha (Penerbit Universiti, UTeM, 2016)
-